Disposable cerium oxide/graphene nanosheets based sensor for monitoring acebutolol in environmental samples and bio-fluids. Issue 2 (April 2022) - Selvi, Subash Vetri; Nataraj, Nandini; Chen, Tse-Wei; Chen, Shen-Ming; Balu, Prakash; Liu, Xiaoheng
Abstract: The production and utilization of medicines strives to be an essential factor in the modern world in treatment, diagnosis and prevention. On the other hand, the medical discharge and the unmetabolized drugs all turns out into environmental polluting agents. The demand for detecting and solving these issues are essential. Herein, we report an electrochemical sensor for quantifying β-adrenoreceptor blocker acebutolol (ACT) in environmental and biological samples. Cerium oxide (CeO2 ) was implied with graphene nanosheets (GNS) as highly conducting material for electrochemically detecting ACT. The structural and morphological studies were studied and electrochemical analysis were also performed to efficiently study oxidation mechanism of ACT at CeO2 /GNS interface. Electrochemical impedance spectroscopy (EIS) proved the higher conducting behavior of CeO2 /GNS. Moreover, CeO2 /GNS/SPCE holds higher surface area with more edge sites facilitating the electro-oxidation of ACT. The linear range of detecting ACT was in the range of 0.039 μM to 486.6 μM. The limit of detection was found to be 0.007 μM with the sensitivity about 27.3 μAμ M −1 cm − 2 . The real samples like river water and urine samples were utilized for real time detection of ACT. Thus, the fabricated electrode with more efficiency and higher conducting property will enhance the real time sensing of ACT in environmental and biological samples. Graphical Abstract: Synthesis of CeO2 /GNS and electro-oxidation of ACT. ga1 Highlights: An efficient electrochemical sensor based on CeO2 /GNS/SPCE was developed for acebutolol detection. The physico-chemical analysis was initiated with XRD, XPS, FESEM and Raman analysis. The linear range was 0.039 μM to 486.6 μM with lower detection limit of 0.007 μM. River water and urine samples were analyzed for real time analysis. The fabricated electrode had excellent selectivity among several compounds.